Manifestación en Barcelona. "Els assistits a la Casa Prsident Macìa saluden al pais del soviets". Series of 2 photos. Copied from CNT collection
Manifestación en Barcelona. "Els assistits a la Casa Prsident Macìa saluden al pais del soviets". Series of 2 photos. Copied from CNT collection.